Sexualidade e sexuação: um estudo psicanalítico com homens penectomizados por câncer de pênis - Oliveira, Luciano Lima de (2010)
This research arises from our restlessness concerning clinical and hospital-related practice involving men suffering from penile cancer who underwent surgical removal of the penis. We perceived that there was dissonance between these men‟s discourse and that one advanced by medical community and psycho-oncologists, centered mainly on sexual functioning as supported by anatomy and physiology. That discrepancy aroused our desire to tackle the issue by means of a master‟s research considering the possibilities of improving with this work a more coherent design for the follow-up of the patients and their experiences related to a serious damage sustained. Our general objective was to evaluate the impact of penectomy on male sexuality; and, as specific objectives to identify possible alternatives found by patients to fulfill the satisfaction drive in face of penile absence, and ascertain where the reflecting impact would end considering virility anchorage points. Leaning on analytical techniques, we tried to listen to these men, avoiding directing their speeches, considering that this was not psychoanalytical sessions. We tried to establish a more coherent design between our research and psychoanalytical practice, a privileged tool adopted by psychoanalytical research if one considers the meaning of this tool as developed by Freud and Lacan. We heard six subjects during their post-surgical evaluation visits, all of them referred by the Urological Service from the Cancer Hospital of the State of Ceará, where we developed our research. The time between surgical procedure and our encounter with subjects ranged from 10 to 36 months, mean age of them being 60.5 years. After each encounter, we took notes of the subjects‟ speeches, and later presented them as a clinical sketch. Thus, we kept ourselves tuned to major issues inherent to patients‟ subjectivities and not to previous knowledge that we could have about those values. As upshots of our investigative work, we can highlight the dissociation between love and desire in the amorous lives of subjects; the struggle of them to rebuild their virile image in face of female counterpart and other men, lacking as they were the strong imaginary force provided by anatomy; the trend to elaborate on life‟s meaninglessness as a result from disease and surgery preventing them from exerting their virility in relation to other women but the wife; the absence of “sexual life” for those who maintain a penile stump, thus disputing the medical knowledge that propounds existence of a capability for sexual pleasure by patients who underwent partial penectomy. We concluded that by means of a psychoanalytical hearing technique it was possible to assess from the subjects‟ discourse that sexuality presents itself to a certain extent resistant to rehabilitating models based solely on its functional dimension, and, therefore, restricted to patient behavior in relation to the sexual act. This disclosed the importance of a more extensive work with those patients without restricting itself to pedagogical interventions, but aiming at making patients elaborate on their loss and help them tackle in a symbolic way their new reality, including bodily configuration.